2010
DOI: 10.5028/jatm.2010.02038910
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation as an alternative for strategic development in the aerospace industry in Brazil

Abstract: We present in this paper a case of technological competence development in the aerospace sector in Brazil, by addressing the complete cycle of integrated circuits for satellite applications, an area of high technology which is strategic to the country. The development of technological and business competences is linked to an understanding of the existing relations between different participating institutions, both public and private. There is an effort to establish a network for the development of radiation-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
7
0
4
Order By: Relevance
“…Embraer is a Brazilian company which produces airplanes internationally [Armellini et al, 2014]. Partnerships between university and business complement the skills needed to improve the performance of the businesses [Azmi, Alavi, 2013;Dewes et al, 2010;Becker, Eube, 2018;Lucia et al, 2012]. Doing so, they will encourage open innovation and collaboration between businesses and universities.…”
Section: Open Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Embraer is a Brazilian company which produces airplanes internationally [Armellini et al, 2014]. Partnerships between university and business complement the skills needed to improve the performance of the businesses [Azmi, Alavi, 2013;Dewes et al, 2010;Becker, Eube, 2018;Lucia et al, 2012]. Doing so, they will encourage open innovation and collaboration between businesses and universities.…”
Section: Open Innovationmentioning
confidence: 99%
“…[Akinwale, 2018;Lopes et al, 2017;Merino et al, 2015;Schuster, Brem, 2015;Scuotto et al, 2020] Mitigation of R&D project failures Reflationary perspective -avoidance of local research bias and fast error identification New business and science evaluation models characterized by open practices allow fast error identification and enable processes improvement. [Jamett et al, 2017;De Pablos-Heredero et al, 2013;Dewes et al, 2010;Gerhart et al, 2000;Strasak et al, 2007;Lee et al, 2012] Importance [ Armellini et al, 2014;Celadon, 2014;Remneland-Wikhamn, 2013;Calderón-Martínez, 2009 Intellectual property management model Exploitative perspective -generation of scientific finding with real-life applications IP management is based on free licenses, for instance CC licenses, in science and enterprises. These licenses amplify the affordability of digital technology and provide an enhanced means for social production in the networked economy.…”
Section: Open Sciencementioning
confidence: 99%
“…Luoma, Paasi, and Valkokari (2010) found that a patent was an important protection method for only 30% of the 40 interviewed firms in Finland and in the Netherlands. In Brazil, the host country of our study, the culture of registering new developments is not common to most industrial sectors (Dewes et al, 2010;Etzkowitz et al, 2008). Therefore, we believe that, in countries where there is limited practice of protecting and negotiating intellectual property, this issue may be a limitation for the complete adoption of open innovation.…”
Section: From Closed To Open Innovation In Emerging Economies: Evidenmentioning
confidence: 99%
“…Regarding innovation activities from emerging economies, such as China and India, open innovation has been studied in terms of patents in co-authorship with inventors from different countries (Pai et al, 2012). In Brazil, open innovation has been studied in the aerospace industry (Dewes et al, 2010) and in a few large firms trying to structure their open innovation strategies as in the cases of Natura, the Brazilian subsidiary of IBM, and Siemens/Chemtech (Ades et al, 2013). Given that the open innovation model was initially adopted by multinational companies -and as a consequence, most of the literature concentrates on large firms located in developed economies -and given the increasing importance of partnerships for firms in emerging economies as ways to overcome barriers to innovation as the limitation of resources, it is a valuable exercise to explore how open innovation is being performed by firms located in emerging countries.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing this integration of approaches to the process of innovation, recent studies have emphasized the growing importance of external sources of ideas on an approach of open innovation (DEWES et al, 2010), which can be defined as the various forms of relationship between innovative companies and external agents (DAHLANDER, GUNN, 2010;DEWES et al, 2010). This type of relationship can be seen in cases such as the cities of Toulouse (France), Seattle (United States) and Montreal (Canada), showing positive results, such as technological and production expertise, and economies of scale identified in the aeronautical sector due to the development of regional productive systems of innovation or technology parks specializing in R&D (ABDI, 2009).…”
Section: Introductionmentioning
confidence: 99%